Validation of the UNESP-Botucatu pig composite acute pain scale (UPAPS) - Luna, Stelio Pacca Loureiro [UNESP]; de Araújo, Ana Lucélia [UNESP]; da Nóbrega Neto, Pedro Isidro; Brondani, Juliana Tabarelli [UNESP]; de Oliveira, Flávia Augusta [UNESP]; dos Santos Azerêdo, Liliane Marinho; Telles, Felipe Garcia [UNESP]; Trindade, Pedro Henrique Esteves [UNESP] (Public Library of Science (PLoS), 2020)
The creation of species-specific valid tools for pain assessment is essential to recognize pain and determine the requirement and efficacy of analgesic treatments. This study aimed to assess behaviour and investigate the validity and reliability of an acute pain scale in pigs undergoing orchiectomy. Forty-five pigs aged 38±3 days were castrated under local anaesthesia. Behaviour was video-recorded 30 minutes before and intermittently up to 24 hours after castration. Edited footage (before surgery, after surgery before and after rescue analgesia, and 24 hours postoperatively) was analysed twice (one month apart) by one observer who was present during video-recording (in-person researcher) and three blinded observers. Statistical analysis was performed using R software and differences were considered significant when p<0.05. Intra and inter-observer agreement, based on intra-class correlation coefficient, was good or very good between most observers (>0.60), except between observers 1 and 3 (moderate agreement 0.57). The scale was unidimensional according to principal component analysis. The scale showed acceptable item-total Spearman correlation, excellent predictive and concurrent criterion validity (Spearman correlation ≥ 0.85 between the proposed scale versus visual analogue, numerical rating, and simple descriptive scales), internal consistency (Cronbach's α coefficient >0.80 for all items), responsiveness (the pain scores of all items of the scale increased after castration and decreased after intervention analgesia according to Friedman test), and specificity (> 95%). Sensitivity was good or excellent for most of the items. The optimal cut-off point for rescue analgesia was ≥ 6 of 18. Discriminatory ability was excellent for all observers according to the area under the curve (>0.95). The proposed scale is a reliable and valid instrument and may be used clinically and experimentally to assess postoperative acute pain in pigs. The well-defined cut-off point supports the evaluator´s decision to provide or not analgesia.